IMPLEMENTASI PERAN STAKEHOLDERS DALAM PENGEMBANGAN PARIWISATA (STUDI KASUS PADA KEPULAUAN BANDA) - Salouw, Elvis (Jurnal Pariwisata Pesona, 2021)
Banda Islands, also known as the "Spice Islands", is a group of spice-producing islands located in central Maluku District. The Banda Islands are included in the UNESCO tentative list as the World Heritage Centre with the criteria (iv), (vi), (x). Banda islands are also included in the National Tourism Destination (DPN) Maluku province and one of the National Tourism Development Area of Indonesia (KPPN). Banda Islands as a tourist destination has been known for a long time because of the diversity of attractions. However, in its development, tourism in the Banda islands has not shown significant results in the last decade. The management of the Banda Islands tourism involves many actors both from the government, private and community sectors. This study was conducted to find out 1) the development of the Banda Islands Tourism Management, 2) identify the participating stakeholders, 3) know the role of each stakeholders and 4) describe the collaboration between stakeholders in Banda Islands Tourism Management. This research uses qualitative methods, primary data collection is done by observation, interviews and Focus Group Discussion (FGD). The selection of respondents in the interview is determined purposive sampling based on consideration and capacity in the tourism management of Banda District. The data analysis technique used in this study is a qualitative descriptive analysis used to qualitatively describe the data obtained from the research site. The results shows that 1) Coordination between stakeholders has not been well so that the role of each stakeholder in tourism management has not shown maximum results, 2) The role of the private sector is too . so that the tourism development carried out by the public sector has not worked well.